ABUNDANCE OF EVERGREEN TREE SPECIES IN A DISTURBED SEASONALLY TROPICAL DRY FOREST - Rodrigo, Ruffy; Cueva, Eduardo (Journal of Agriculture and Technology Management; Journal of Agriculture and Technology Management (JATM) Volume 20 Issue 2, July-December 2017, 2018)
The study was conducted to determine the abundance of evergreen tree species in the tropical dry forest in Southern Ecuador. Systematic sampling approach was adapted for this study. Twenty-five plots with 531 m 2 sampling size were laid out in the disturbed forest. Results showed that there were only a few evergreen tree species recorded in the study area. The family Fabaceae was dominant among the recorded trees. In addition, an increasing pattern of stem density from low to high elevation was noted, but a decreasing pattern of the basal area was also observed. The study showed that disturbance clearly influences the composition and structure of a tropical dry forest ecosystem.